Long-Term Effects of the Harvesting of Trapa natans on Local Water Quality and Aquatic Macrophyte Community in Lake Erhai, China - Yuan, Changbo; Bai, Xiaohu; Zhu, Tianshun; Wen, Zihao; Cao, Te; Zhang, Xiaolin; Ni, Leyi (Frontiers in Environmental Science, 2021)
Trapanatans is one of the main species causing the swamping in the littoral zones of Erhai Lake. It commonly forms a dense canopy on the water surface in the growing season (June–September), which hampers the local water quality and habitat of submerged macrophytes, and releases nutrients to the water after death in autumn and winter, resulting in the deterioration of local water quality. At present, there are many and positive research studies on the short-term effects of harvesting water chestnut on water quality and aquatic plants, but long-term observation results are lacking. In response to the above problems, we studied responses of water quality and aquatic plant community to the removal of Trapa in littoral zone of a northern bay in Erhai from August 2014 to January 2017. This could be the first attempt to discover the long-term effects of floating-leaved vegetation management in the freshwater ecosystem. The results showed that the artificial removal of Trapa significantly improved the local water quality in the growing season, for example, the concentrations of total nitrogen (TN), dissolved nitrogen (DN), total phosphorus (TP), and dissolved phosphorus (DP) in the non-Trapa zone (NTZ) were much lower than the concentrations of those in the adjacent Trapa zone (TZ). And the biomass of aquatic macrophyte community (BAMC) was significantly increased in the NTZ, up to the maximum value of about 21 kg/m2 in fresh weight. However, the diversity indexes of the community in the NTZ declined. Therefore, we suggested that although the removal of Trapa improved the water quality and increased the productivity of the submerged aquatic plant community, it reduced the species diversity of the aquatic plant community in the long run. This is another issue that we need to pay attention to in the later management in Erhai Lake.